Metode Induksi Dalam Penalaran Sederhana Untuk Meningkatkan Pembelajaran PAI Yang Kritis Bagi Generasi Millenial Abad 21 - Hanif Abdul Rahman; Tri Wahtudi Fajar Prabowo; Habibatur Rahmah Arief S; Moh Faizin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to examine the application of the induction method in simple reasoning as an effort to improve critical Islamic Religious Education (PAI) learning for the 21st century millennial generation. This induction method is very useful for educators in carrying out the learning process in the classroom, because as we already know, this induction method is a method that focuses on crisis thinking patterns from specific cases to general conclusions and is considered quite relevant for building critical and analytical thinking skills in students. The use of the induction method in PAI learning is able to encourage students to be more active in analyzing religious issues, connecting concepts with real life realities, and building logical and value-based arguments. Apart from that, this method also strengthens the relevance of PAI learning to the challenges and needs of the millennial generation, such as critical thinking, collaboration and the use of technology. Thus, the induction method can be a strategic alternative in developing PAI learning that is more contextual and in line with the demands of the 21st century